The Relationship Between Lato-Lato Games And Decreased Gadget Use In Elementry School Age Children In Jati Kesuma village, Namorambe District Deli Serdang District, North Sumatera Province - Samura, Maximilianus Dasril; Indah Febi Claudia (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
The development of an increasingly advanced era at this time resulted in more and more changes that occur in people's lives. In the current era of globalization, there are many types of developments ranging from developments in science, technology to political, economic and cultural developments. Technology that is very popular in this era of globalization is gadget. Gadgets were once only used by the upper middle class, but their use is now used by various groups, ranging from early childhood to adults. The research method used in this study is an analytical survey with a cross sectional approach. namely research that emphasizes the time of measurement or observation of data on the dependent variable and the independent variable is calculated at the same time or once. Factors that influence the level of lato-lato play with the use of gadgets include: parental age, parental education, child age and child gender. The results of statistical tests using the Chi Square test obtained a p value of 0.002. So that the p value ? 0.05. Based on statistical tests, it can be seen that there is a significant relationship between lato-lato games and decreased gadget use in elementary school-age children in Jati Kesuma Village, Namorambe District, so that the results of statistical tests can be interpreted as Ho is rejected. And from the results of the above research, it can be suggested to parents to be aware of their children in the use of gadgets and more suggest to children to play games that can stimulate motor development and social development of children in the future.